Pengaruh Penambahan Maltodekstrin dan Tween 80 terhadap Karakteristik Bubuk Minuman Instan Daun Jeruju (Acanthus Ilicifolius L.) - Adi Mahendra, Sang Made; Diah Puspawati, Gusti Ayu Kadek; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Abstract The purpose of this research was to determine the concentration effect of maltodextrin and tween 80 on the characteristics of the jeruju leaf instant drink powder and to proper concentration of maltodextrin and tween 80 to get the jeruju leaf instant drink powder with the best characteristics. The research used a factorial randomized block design with 2 factors. First factor was concentration of maltodextrin that consisting of 3 levels (10%, 15% and 20%) and second factor was concentration of tween 80 that consisting of 3 levels (0.3%, 0.4% and 0.5%) so there were 9 treatment combinations. The repetition of each treatment combination was carried out 2 times, in order there were 18 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed of parameters, it was continued with Duncan's Multiple Range Test. The result showed that interaction of the concentration of maltodextrin and tween 80 had a significant effect (P<0,05) on the moisture content, ash content, solubility, solubility time, total phenol, and antioxidant activity.Each concentration of maltodextrin and tween 80 had a very significant effect (P<0.01) on yield. The concentration of 20% maltodextrin and 0.5% tween 80 it was the best treatment to produce jeruju leaf instant drink powder with a yield of 11.81%, water content of 4.7%, ash content of 1.25%, solubility of 92.55%, dissolving time of 16.42 seconds, total phenol 19.27 mgGAE/g powder, antioxidant activity of 66.25%, sensory assessment of color was liked, aroma that was kinda of liked with a somewhat distinctive aroma characteristic of jeruju leaf, taste that was kinda of liked with a somewhat distinctive taste characteristic of jeruju leaf, and the overall acceptance was liked.